Enamel paste composition, enamel-coated product and method for manufacturing thereof
Patent Information
- Application Number
- CN202280029765.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-21
- Filing Date
- 2022-04-14
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-04-14
AI Technical Summary
即,US20170135160发现,输送至母线的功率没有完全传输到导电层,这导致功率损失,对玻璃板的加热性能产生不利影响
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004503080790000051
Abstract
Description
Technical Field
[0001] This invention relates to enamel paste compositions, enamel-coated products, and methods for manufacturing the same. Background Technology
[0002] In the automotive glass industry, windshields, taillights, sidelights, and other glass components are typically decorated with a black masking enamel strip extending around the outer perimeter of the component. A primary function is to protect the adhesive holding the glass component in place from UV radiation, which would otherwise cause the adhesive to decompose. A secondary function is to cover circuitry, wiring, and connectors to ensure the functionality of the electrical or electronic components connected to or embedded in the glass component, and to ensure a clean and aesthetically pleasing appearance.
[0003] Enamelled enamel typically comprises glass frit and pigments in an organic carrier medium. In screen printing or inkjet processes, enamel is applied to a flat glass substrate in the form of a paste or ink, followed by firing at a high temperature. During this process, the organic carrier medium of the paste or ink burns away, and the enamel fuses together, establishing a bond with the substrate. The firing process also softens the substrate, allowing it to be shaped into its final form during the firing process. A two-step firing process is also known to form the enamel layer, comprising: (i) a first “pre-firing” heating step at a temperature below the melting temperature of the glass frit in the enamel paste to remove the organic carrier medium components of the enamel paste, thereby forming a dry pre-firing layer; and (ii) a second “firing” heating step at a temperature above the melting point of the glass frit in the enamel paste to fuse the enamel. During the second firing step, the substrate can be shaped into its final form by a bending process.
[0004] In addition to shielding enamel, electrical components can be printed onto glass components in a similar manner. In this case, the enamel formulation typically includes a metallic conductive powder (e.g., silver powder), a glass frit, and an organic carrier medium. This conductive enamel paste can be applied together with the shielding enamel paste and fired in the same process to form a glass component comprising electrical components (e.g., antennas and / or heating elements) and the shielding enamel, which is arranged to shield electrical connections (e.g., busbars) to the electrical components.
[0005] Recently, functional thin films have also been applied to glass components, for example using vapor deposition processes. These functional thin films have nanometer-scale thicknesses and can be used, for example, as heating elements (replacing more traditional screen-printed or inkjet-printed conductive silver ceramic enamel heating wires) and / or IR reflective elements.
[0006] US20170135160 (authorized as US10455645B2) describes an example of a method for manufacturing a glass plate for a motorized vehicle, the glass plate including a sputtering system for heating the glass plate. The glass plate configuration described in US20170135160 is as follows: Figure 1 As shown, the device comprises two glass sheets 2 and 4 joined together by an intermediate layer 6. In use, glass sheet 2 forms the outer glass sheet of the glass plate, while glass sheet 4 forms the inner glass sheet. The sides of the glass sheets in a motor vehicle glass plate are typically numbered from the outside to the inside. Thus, the outer side 8 of the outer glass sheet 2 is typically designated as side 1, the inner side 10 of the outer glass sheet 2 is typically designated as side 2, the side 12 of the inner glass sheet 4 facing the outer glass sheet 2 is typically designated as side 3, and the inner side 14 of the inner glass sheet 4 is typically designated as side 4. Figure 1 In the configuration shown in US20170135160, a ceramic enamel layer 16 is formed on the side surface 2 of an outer glass sheet. A thin coating layer 18 is formed over the ceramic enamel layer 16 and over the uncoated portion of the side surface 2 of the outer glass sheet. In US20170135160, the thin coating layer is a system of heated conductive layers formed by cathode sputtering and includes an assembly of a metal layer and a dielectric layer, which may have a thickness of 0.1 micrometers or less. An electrical busbar 20 is then formed on the thin coating layer 18 over the ceramic enamel layer 16. As previously stated, US20170135160 discloses that the system can be fired in a two-step firing process, including a first pre-firing step for removing the organic carrier medium and a second firing step at a higher temperature for melting and fusing the glass frit, wherein bending is performed in the second firing step of the firing process to form a shaped glass article.
[0007] US20170135160 has been released. Figure 1 One problem with the configuration shown and described above is that, as US20170135160 found, the power delivered to the busbar is not fully transferred to the conductive layer, resulting in power loss and adversely affecting the heating performance of the glass plate. US20170135160 states that this problem is at least partly caused by the surface roughness of the enamel layer, which adversely affects the conductive coating covering it and the connection between the busbar and the conductive coating above the enamel layer. Therefore, US20170135160 describes the surface roughness R of the enamel layer. aThe roughness should not exceed 0.5 micrometers, and preferably not exceed 0.1 micrometers. Several methods for reducing the roughness of the enamel layer are described, including: (i) using an enamel composition comprising glass frit and pigment, wherein the average particle size of the pigment and optionally the glass frit is not greater than 5 micrometers; (ii) using a printing screen with a coating surface having low surface roughness to screen print the enamel paste; (iii) changing the surface tension and viscosity in the applied enamel paste layer to provide a smooth effect; and (iv) inkjet printing the enamel instead of using screen printing.
[0008] US20170135160 describes a ceramic enamel paste composition that is not application-specific. It discloses an average roughness R for ceramic enamel layers produced by screen printing. a The roughness was 0.69 micrometers (too rough, above the 0.5 micrometer threshold). For layers applied by inkjet technology, the roughness was significantly reduced, and an average roughness on the order of 0.14 micrometers was achieved using enamel compositions produced by Johnson Matthey (JM1L6027).
[0009] This invention relates to an improved enamel paste composition specifically tailored for use with, for example, the method described in US20170135160. Summary of the Invention
[0010] As described in the background section, US20170135160 states that, apart from the particle size of the glass frit and pigments and the viscosity of the enamel paste provided by the organic carrier medium, the composition of the enamel paste is not specific for use with functional thin coatings. Apart from using commercially available enamel compositions from Johnson Matthey, US20170135160 provides no information about the type of glass frit used in the enamel. Furthermore, there is no indication that the chemical composition of the glass frit has any effect on the surface roughness of the enamel and subsequently on the functional thin coating deposited thereon. Instead, US20170135160 states that a smoother enamel surface can be achieved by using pigments with smaller particle sizes in the enamel composition and also suggests modifications to the printing process used for depositing the enamel.
[0011] The inventors have developed an improved enamel paste formulation for the application described in US20170135160. Specifically, the improved enamel paste formulation comprises a composition having the following characteristics:
[0012] (i) A glass composition having a low firing (melting) temperature, which allows the glass to soften and flow at a low firing temperature in order to provide a smooth enamel layer for applying a thin coating thereon at a low temperature;
[0013] (ii) A glass composition having a high crystallization temperature, such that the glass enamel does not crystallize and damage the functional thin coating disposed thereon during heating and bending of the coated glass article;
[0014] (iii) A glass composition that satisfies the characteristics of (i) and (ii) and also has good silver hiding and UV blocking properties after heating and bending the coated glass article.
[0015] In other words, the chemical composition of the glass frit component in the enamel paste affects the quality of the thin coating deposited thereon and the resulting coated glass articles. Specifically, the glass frit must be adjusted to have a low firing temperature and a high crystallization temperature to produce a surface enamel layer with low roughness and to prevent damage to the functional thin coating during deposition and further processing of the coated glass articles (i.e., during heating and bending). The enamel must also possess good silver hiding and UV blocking properties, which are influenced by the type of glass frit, firing temperature, and pigments.
[0016] Therefore, the present invention provides a ceramic enamel paste composition specifically for applying a functional thin coating thereon. The ceramic enamel paste comprises:
[0017] 30 to 40% by weight of bismuth silicate glass frit,
[0018] 20 to 30% by weight of zinc silicate glass frit,
[0019] 15 to 25% by weight of pigment, and
[0020] 10 to 20% by weight of organic carrier medium;
[0021] The bismuth silicate glass material described herein comprises at least silicon, bismuth, boron, and lithium, and is free of lead and cadmium.
[0022] The zinc silicate glass frit contained at least silicon, zinc, sulfur, and lithium, and contained no lead, cadmium, or bismuth.
[0023] The glass frit and pigment in the enamel paste each have a D90 particle size distribution of less than 15 micrometers, and
[0024] The porcelain glaze paste is applied in 100 seconds. -1 It has a shear rate of 5 to 150 Pa·s -1 The viscosity between them.
[0025] Zinc silicate glass imparts silver-hiding properties to the enamel. Bismuth silicate glass allows the enamel to be processed at low temperatures and forms a smooth surface at low firing temperatures. The glass also possesses a high crystallization temperature. Therefore, the combination of the two glasses provides a smooth surface at low firing temperatures, silver-hiding properties over a wide temperature range, and a high crystallization temperature.
[0026] Optionally, the bismuth silicate glass frit has the following composition (expressed as oxide component):
[0027]
[0028] Optionally, the zinc silicate glass frit has the following composition:
[0029]
[0030] The pigment is optionally a CuCr black pigment.
[0031] The present invention also provides the use of a ceramic enamel paste for manufacturing coated glass articles, the coated glass articles comprising a glass substrate, a ceramic enamel layer disposed on the glass substrate, and a thin coating layer disposed on the ceramic enamel layer with a thickness not greater than 0.5, 0.4, 0.3, 0.2, or 0.1 micrometers.
[0032] The enamel paste is tailored for a method of manufacturing coated glass articles, including but not limited to the types of coated glass articles described in US20170135160. The method includes:
[0033] Deposit a ceramic paste onto a portion of a glass substrate;
[0034] The porcelain glaze paste is fired at temperature T1 to form a porcelain glaze layer;
[0035] A thin coating is deposited over at least a portion of the enamel layer, the thickness of which is no greater than 0.5, 0.4, 0.3, 0.2, or 0.1 micrometers;
[0036] A glass substrate with a porcelain enamel layer and a thin coating is fired and bent at a temperature T2 greater than T1 to form a coated glass article.
[0037] The glaze paste is formulated to have a firing temperature below T1 and a crystallization temperature above T2.
[0038] The paste composition described above can be used in this method. However, it is also conceivable that the firing temperature T1 and bending temperature T2 may differ for different applications. In this case, the formulation of the enamel paste can be modified to ensure that it has a firing temperature below T1 and a crystallization temperature above T2, so as to ensure that the thin film coating applied to the enamel is not damaged during processing, while achieving the color characteristics and / or silver hiding properties required for the final application after processing at T2. Therefore, the method of the present invention is not limited to a specific enamel paste composition tailored for a final application with specifically defined T1 and T2. That is, those skilled in the art of enamel paste formulation will be able to utilize the teachings of the present invention to modify the composition of the paste described herein, thereby adapting it to thin film coating applications with different T1 and T2 values and utilizing different bending processes (including, for example, sag bending, press bending, and variations thereof).
[0039] Advantageously, the roughness R of the glaze layer a Not greater than 1, 0.7, 0.5, or 0.3 micrometers and / or roughness R z The value should not exceed 5, 4, 3, 2, or 1 micrometer. Furthermore, for masking applications, the enamel layer advantageously has an L value not exceeding 5, 4.5, 4, or 3.5.
[0040] The thin coating can be deposited using vacuum deposition processes, such as cathode sputtering, as described in the application in US20170135160. In addition to being deposited over at least a portion of a ceramic enamel layer, the thin coating can also be deposited over at least a portion of a glass substrate. Furthermore, as described in US20170135160, the thin coating can be conductive, optionally comprising multiple sublayers (e.g., two or three silver sublayers), and at least one electrical connector can be deposited on the thin coating over the ceramic enamel layer.
[0041] While the enamel paste of the present invention has been developed for applications such as those described in US20170135160, it is conceivable that the enamel paste of the present invention can be used for other functional thin film coatings on glass substrates, including electrical, optical and thermal functional coatings. Brief description of the attached diagram
[0043] To better understand the present invention and illustrate how to implement it, certain embodiments of the invention will now be described by way of example only with reference to the accompanying drawings, in which:
[0044] Figure 1 The configuration of automotive glass panels of the type described in US20170135160 is shown;
[0045] Figure 2 Showing the provision for Figure 1 A flowchart illustrating the steps involved in the coating of the glass sheet in the automotive glass panel configuration shown.
[0046] Figure 3(a) and 3(b) A flowchart is shown, illustrating the following... Figure 2 The method causes film damage during processing unless the firing (melting) temperature of the enamel paste composition is lower than the firing temperature T1 and the crystallization temperature of the enamel paste composition is higher than the bending temperature T2.
[0047] Figure 4 The color development properties of the enamel layer formed using the enamel paste composition of the present invention are shown in terms of its L value and firing temperature. This enamel is formulated to have a low L value and not crystallize at the final firing (bending) temperature T2 of the coated glass manufacturing process; and
[0048] Figure 5 The silver hiding properties of the enamel layer formed using the enamel paste composition according to the invention are shown in relation to its dE value and firing temperature, the enamel being formulated to have a low dE value (good silver hiding) and not crystallize at the final firing (bending) temperature T2 of the coated glass manufacturing method. Detailed Implementation
[0049] As described in the background section, the glass plate configuration described in US20170135160 is as follows: Figure 1 As shown, the glass sheet comprises two glass sheets 2 and 4 joined together by an intermediate layer 6. The outer side 8 of the outer glass sheet 2 is typically designated as side 1, the inner side 10 of the outer glass sheet 2 is typically designated as side 2, the side 12 of the inner glass sheet 4 facing the outer glass sheet 2 is typically designated as side 3, and the inner side 14 of the inner glass sheet 4 is typically designated as side 4. A enamel layer 16 is formed on the side 2 of the outer glass sheet. A thin coating layer 18 is formed above the enamel layer 16 and above the unenamel portion of the side 2 of the outer glass sheet. An electrical busbar 20 is formed on the thin coating layer 18 above the enamel layer 16. The glass sheets 2 and 4 are fired and shaped, and then laminated with the intermediate layer 6 to form a glass plate.
[0050] It should be noted that, although Figure 1 The configuration shown has a enamel layer 16 and a thin coating layer 18 disposed on the side 2 of a laminated glass plate comprising two glass sheets 2 and 4, but the invention is not limited to this configuration. For example, the enamel layer and the thin coating layer can be applied to different sides of such a laminated glass plate, or they can be applied to a glass plate comprising a single glass sheet.
[0051] Figure 2 Display provided Figure 1The flowchart illustrates the steps involved in coating the outer side of the glass sheet 2 of the automotive glass panel configuration shown. The method includes: depositing a ceramic paste on the side surface 2 of the outer glass sheet; firing at a temperature T1°C; applying a thin coating layer over the ceramic paste and over the uncoated portions of the outer glass sheet; applying silver wire mesh to the thin coating layer over the ceramic paste portions of the outer glass sheet; and bending the coated glass sheet at a temperature T2°C.
[0052] Figure 3(a) and 3(b) The flowchart shown illustrates the following Figure 2 The method can cause damage to the thin film coating during processing unless the firing (melting) temperature of the enamel paste composition is lower than the firing temperature T1 and the crystallization temperature of the enamel paste composition is higher than the bending temperature T2.
[0053] Figure 3(a) shows that if the enamel paste is initially fired at a temperature T1 below the firing / melting temperature of the glass frit (which is the case in a standard pre-firing step designed to remove only the organic carrier medium without melting and fusing the glass frit), a rough surface is produced, which can lead to damage to the film coated on such a surface when deposited using, for example, vapor deposition techniques.
[0054] Figure 3(b) shows that even if the enamel paste is initially fired at a temperature T1 higher than the firing / melting temperature of the glass frit to provide a smooth surface (on which a thin film coating is deposited), the thin film coating can be subsequently damaged during the bending of the coated glass sheet if the bending temperature T2 is higher than the crystallization temperature of the glass enamel.
[0055] Thus, Figures 3(a) and 3(b) show that the glass frit in the enamel composition must have a firing / fusion / melting temperature below T1 to produce a low surface roughness after firing at T1, and a crystallization temperature above T2 to ensure that the thin film coating is deposited in an undamaged form and remains undamaged during processing (bending) at T2.
[0056] In addition to the above, the resulting glaze must meet the functional characteristics required for its application. For example, in Figure 1In automotive glass applications, the enamel must possess excellent optical properties and good silver hiding properties to: (i) protect the adhesive / binder from UV degradation; and (ii) shield the silver busbars arranged behind the enamel. These properties depend on the chemical composition of the glass frit and also on the final firing / bending temperature T2 of the glass sheet used to process the enamel coating. Therefore, for this application, the enamel paste composition must be tailored to meet several requirements, including firing / melting / melting temperatures below T1, crystallization temperatures above T2, and also to meet the optical properties and silver hiding properties required for the final application after processing at T2. The enamel must also be chemically and structurally resistant to thin-film coating and vapor deposition methods used to create thin-film coatings over the enamel. Furthermore, for automotive applications, the enamel must be acid-resistant (0.1 N H2SO4, for 4 hours at 80 °C), and the coated glass sheet must meet minimum mechanical strength specifications.
[0057] The present invention provides a ceramic enamel paste composition that meets all the above-mentioned requirements for use in combination with a functional thin coating (e.g., a self-heating coating or an IR-reflective coating).
[0058] The enamel paste comprises: (1) bismuth silicate glass frit; (2) zinc silicate glass frit; (3) pigment; and (4) organic carrier. Details of examples of two glass frit compositions with respect to equivalent oxides are provided below.
[0059] Bismuth silicate glass material:
[0060]
[0061] Zinc silicate glass material:
[0062]
[0063] The pigment can be an automotive black pigment, such as CuCr black pigment.
[0064] The glass frit and pigment are ground to the desired particle size distribution with D90 < 15 micrometers and mixed with an organic carrier formulation to produce a product that yields a product in 100 seconds. -1 Viscosities at shear rates ranging from 5 to 150 Pas -1 The paste between them.
[0065] The following table provides examples of paste formulations:
[0066] Glass material 1 Pb / Cd / Bi Zn / S / Li glass frit 25.6 Glass Material 2 Pb / Cd Li / Bi / Si glass frit 38.4 pigment Black pigment 21.4 organic media Solvent / Diluent / Thixotropic Agent 14.6
[0067] The novelty of this paste formulation lies in its ability to impart a subtle combination of properties to the enamel, adapting to the production process of laminated glass panels for self-heating motorized vehicles. Self-heating windshields are relatively new products that have been introduced to the market in the past five years at the time of writing, and this invention improves the performance of such windshields.
[0068] As previously mentioned, key characteristics of porcelain enamel paste formulations include: (i) low firing temperature; (ii) a smooth surface after firing; (iii) good silver hiding properties; and (iv) high crystallization temperature. Zinc silicate glass frit provides the porcelain enamel with silver hiding properties. Bismuth silicate glass frit allows the porcelain enamel to be processed at low temperatures and forms a smooth surface at low firing temperatures. Both glass frits have high crystallization temperatures. Therefore, the combination of the two glass frits provides a smooth surface at low firing temperatures, silver hiding properties over a wide temperature range, and a high crystallization temperature to prevent crystallization during the bending of the coated glass sheet. This combination of characteristics enables the application of a nanoscale silver coating over the porcelain enamel, which can then withstand bending processes without damage.
[0069] In addition to the above, the enamel paste composition, after firing at T2, provides an enamel layer with good optical and silver-concealing properties. Figure 4 The color characteristics of the enamel layer formed using the enamel paste composition with respect to its L value and firing temperature are shown. The enamel is formulated to have a low L value and not crystallize at the final firing (bending) temperature T2 of the coated glass manufacturing method. Figure 5 The silver hiding properties of the enamel layer formed using the enamel paste composition are shown in relation to its dE value and firing temperature. The enamel is formulated to have a low dE value (good silver hiding) and not crystallize at the final firing (bending) temperature T2 of the coated glass manufacturing method.
[0070] Therefore, the resulting paste can be used to construct laminated glass panels for improved motorized vehicles. The enamel paste is deposited onto a glass substrate (typically soda-lime glass), dried and fired at a given temperature to obtain a smooth enamel surface. Subsequently, a thin, multilayered silver coating is deposited over the glass sheet and enamel to form a resistance heating element or IR reflection barrier, followed by the deposition of a busbar over the enamel in contact with the thin coating. The coated glass sheet is then heated and bent to form a shaped windshield component.
[0071] The specific paste composition described above has been tailored to the manufacturing process of a specific windshield with specific T1 and T2 temperatures. However, it is also conceivable that the firing temperature T1 and bending temperature T2 may differ for different applications. In this case, the formulation of the enamel paste can be modified to ensure that it has a firing temperature below T1 and a crystallization temperature above T2, thereby ensuring that the thin film coating disposed on the enamel is not damaged during processing, while also achieving the color characteristics required for the final application after processing at T2. Therefore, the method of the present invention is not limited to a specific enamel paste composition tailored for a final application with specifically defined T1 and T2. That is, those skilled in the art of enamel paste formulation will be able to utilize the teachings of the present invention and modify the enamel paste composition described herein to suit thin film coating applications with different T1 and T2 values. The key essential characteristic of any modified paste is that the formulation of the enamel paste has a firing temperature below T1 and a crystallization temperature above T2 to ensure that the thin film coating disposed on the enamel is not damaged during processing, and also to ensure that it achieves the desired optical properties required for the final application after processing at T2. Variations of the examples described herein can achieve functional changes for such end applications. Therefore, variations can fall within the scope of the glass composition defined in the summary section, although combinations of different glass types are also conceivable to satisfy the functional requirements of the methods described herein. Thus, while the invention has been specifically shown and described with reference to certain examples, those skilled in the art will understand that various changes in form and detail may be made without departing from the scope of the invention as defined by the claims.
Claims
1. A porcelain glaze paste, said porcelain glaze paste comprising: 30 to 40% by weight of bismuth silicate glass frit, 20 to 30% by weight of zinc silicate glass material, 15 to 25% by weight of pigment, and 10 to 20% by weight of organic carrier medium; The bismuth silicate glass material described herein comprises at least silicon, bismuth, boron, and lithium, and is free of lead and cadmium. Furthermore, the bismuth silicate glass material described herein has the following composition: The zinc silicate glass frit contained at least silicon, zinc, sulfur, and lithium, and contained no lead, cadmium, or bismuth. The zinc silicate glass frit mentioned above has the following composition: The glass frit and pigment in the enamel paste each have a D90 particle size distribution of less than 15 micrometers, and The porcelain glaze paste is applied in 100 seconds. -1 It has a shear rate of 5 to 150 Pa·s -1 The viscosity between them.
2. The porcelain glaze paste according to claim 1, wherein the pigment is CuCr black pigment.
3. Use of the enamel paste according to any one of the preceding claims for manufacturing coated glass articles, wherein the coated glass articles comprise a glass substrate, an enamel layer disposed on the glass substrate, and a thin functional coating with a thickness not greater than 0.5 micrometers disposed on the enamel layer.
4. A method for manufacturing a coated glass article, the method comprising: Deposit the ceramic enamel paste according to claim 1 or 2 on a portion of a glass substrate. The glaze paste is fired at temperature T1 to form a glaze layer. A thin functional coating is deposited over at least a portion of the enamel layer, the thin coating having a thickness of no more than 0.5 micrometers. A glass substrate with a porcelain enamel layer and a thin functional coating is fired and bent at a temperature T2 higher than T1 to form a coated glass article. The enamel paste is formulated to have a melting temperature below T1 and a crystallization temperature above T2.
5. The method according to claim 4, wherein the enamel layer has a surface roughness R of not more than 1 micrometer. a and / or a surface roughness R of no more than 5 micrometers z .
6. The method according to claim 4 or 5, wherein the enamel layer has an L value of not more than 5.
7. The method according to claim 4 or 5, wherein the thin functional coating is deposited over at least a portion of the enamel layer and also over at least a portion of the glass substrate.
8. The method according to claim 4 or 5, wherein the thin coating is conductive, and at least one electrical connector is deposited on the thin coating above the enamel layer.
9. The method according to claim 4 or 5, wherein the thin coating comprises a plurality of sublayers.
10. The method according to claim 4 or 5, wherein the thin coating is deposited by a vacuum deposition process.
11. The method according to claim 4 or 5, wherein the thin coating has a thickness of not more than 0.4 micrometers.
12. The method of claim 11, wherein the thin coating has a thickness of not more than 0.3 micrometers.
13. The method of claim 12, wherein the thin coating has a thickness of not more than 0.2 micrometers.
14. The method of claim 13, wherein the thin coating has a thickness of not more than 0.1 micrometers.
15. Coated glass articles manufactured by the method according to any one of claims 4 to 14.
Citation Information
Patent Citations
Heated glass panel
US10455645B2
Heated glass panel
US20170135160A1
Improved glass compositions
WO2005073140A1